Carbon / carbon heating element for single crystal furnace and preparation method of carbon / carbon heating element

By using alternating layering of carbon cloth and mesh tires and a variety of high-temperature treatment processes in the single-crystal furnace heating body, a carbon/carbon heating body with high resistivity stability, improved thermal conductivity and corrosion resistance was prepared, and the current solution was solved There are problems such as unstable resistivity, low thermal conductivity, poor silicon corrosion resistance and short service life during use, which achieves the long-term use of the heating element.

CN119430978APending Publication Date: 2025-02-14XIAN CHAOMA SCI TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411582703.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the use of the existing single crystal furnace heating body, there are problems such as unstable resistivity, low thermal conductivity, poor silicon corrosion resistance and short service life, which is difficult to meet the needs of high-temperature non-isothermal heating and oxygen reduction of single crystal furnaces.

Method used

The three-dimensional structure heating body prefabricated by alternate laying of carbon cloth and mesh tires is prepared by chemical vapor-phase penetration and dense treatment, asphalt or resin impregnation-carbonization density treatment, high vacuum high temperature graphitization treatment and mechanical processing technology, suitable preparation Carbon/carbon heating body with high temperature resistivity, thermal conductivity and flexural strength, and a corrosion-resistant conductive coating is prepared on the surface.

Benefits of technology

The high resistivity stability, improved thermal conductivity, excellent antioxidant performance and improved corrosion resistance of the heating body are achieved, and the service life of the heating body is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430978A_ABST
    Figure CN119430978A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of heating bodies for single crystal Czochralski furnaces, and particularly relates to a carbon / carbon heating body for a single crystal furnace and a preparation method of the carbon / carbon heating body. The preparation method comprises the following steps: alternately laying a high-proportion coefficient carbon cloth and a mesh tire, needling in the interlayer direction to prepare a three-dimensional structure heating body preform, drying and hardening the obtained heating body preform, then compacting the preform through high-proportion chemical vapor infiltration and low-proportion impregnation-carbonization until the density is greater than or equal to 1.65 g / cm < 3 >, and thus obtaining the three-dimensional structure heating body. And finally, preparing a composite corrosion-resistant conductive coating on the surface of the carbon / carbon heating element, thereby obtaining the carbon / carbon heating element with the resistivity similar to that of a graphite material and a stable resistance temperature coefficient, obviously prolonging the service life of the carbon / carbon heating element in a silicon corrosion environment of a single crystal furnace, reducing the oxygen content in a crystal pulling process, and improving the production efficiency. And the crystal pulling quality is improved, and the cost of the heating body component is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heating elements for single crystal vertical pulling furnaces, and in particular relates to a charcoal / charcoal heating element for single crystal furnaces and a preparation method thereof. Background Art

[0002] The thermal field of a CZ single crystal furnace refers to the entire temperature field system for melting silicon materials and maintaining a certain temperature for single crystal growth. The distribution of the thermal field temperature zone directly affects whether the crystal pulling production can proceed smoothly, as well as the pulling speed and quality (low oxygen content) of the crystal rod. The heating element, as the core component of the heating system, serves as the heat source of the entire thermal field through its own heat generation, so it is also the most core component of the entire thermal field. For the heating element of a single crystal furnace, important factors include suitable high temperature resistivity, stable resistance temperature coefficient, high thermal conductivity coefficient, excellent mechanical properties, and good corrosion resistance.

[0003] The heating elements used in single crystal silicon furnaces are mostly made of isostatic graphite, but the flexural strength of isostatic graphite heating elements is only 1 / 3 of that of carbon / carbon materials. Therefore, they are prone to cracking and failure during use, and their average lifespan is only 3 to 4 months. At present, many companies have proposed using C / C composites to replace graphite to prepare single crystal thermal field heating elements, but during the use of the prepared heating elements, problems such as unstable resistivity, low thermal conductivity, and poor silicon corrosion resistance have emerged.

[0004] Chinese patent CN10163797513 discloses a method for preparing a heating element for a polycrystalline furnace by chemical vapor infiltration and resin impregnation carbonization densification. The disadvantages of the method are as follows: (1) The high temperature treatment temperature of the polycrystalline heating element is 1500-2300°C, aiming to prepare a high resistivity of 20-50μΩ·m; however, in a single crystal furnace, the resistivity of the heating element prepared by using carbon / carbon composite materials instead of graphite is required to be less than 15μΩ·m; (2) The mechanical processing structure of the heating element prepared by the patent is cylindrical or U-shaped, and the entire thermal field is a uniform temperature environment; it cannot meet the requirements of non-isothermal heating and oxygen reduction of the carbon / carbon heating element of the single crystal furnace; (3) The patent performs chemical vapor deposition coating treatment on the surface of the heating element to resist corrosion by SiCl4 and H2 at 1250°C; however, the operating environment temperature of the single crystal heating element is ≥1650°C, and it resists silicon vapor corrosion at high temperatures.

[0005] Chinese patent CN102391009A discloses a carbon / carbon composite material heating element for a single crystal silicon furnace. The heating element is prepared by pre-oxidation, carbonization, deposition, impregnation, machining and high-temperature treatment. The disadvantages are: (1) the heating element is a conductive material, and the long fibers are equivalent to the "highway" for electrons. However, the short fibers are used as the reinforcing material, and the fibers are short-range disordered, which is not conducive to conductivity; (2) the reinforcing phase of the heating element is made of fiber felt, which cracks during the impregnation and high-temperature process, and sparks are prone to occur when electrons are transmitted between layers; (3) the preform structure needs to be placed on a graphite mold during deposition, resulting in uneven deposition density inside and outside the cylindrical preform, which will inevitably lead to uneven heating during use of the heating element. Summary of the invention

[0006] Based on the deficiencies of the prior art, the present invention provides a carbon / carbon heating element for a single crystal furnace and a preparation method thereof. The heating element has suitable high-temperature resistivity, high resistance stability, high thermal conductivity and flexural strength, as well as excellent corrosion resistance and long service life.

[0007] Specifically, the present invention provides the following technical solutions:

[0008] A method for preparing a carbon / carbon heating element for a single crystal furnace comprises the following steps:

[0009] (1) Alternately layering carbon cloth and mesh tires, needle punching in the interlayer direction (so that the fibers of the mesh tire are brought into the interior of the carbon cloth during the needle punching action) to form a three-dimensional structure heating element preform, and then drying and hardening the obtained heating element preform; in the heating element preform, the content of carbon cloth is 70-90wt%, and the content of mesh tire is 10-30wt% (the higher the content of carbon cloth, the more high-speed channels for electron transmission, which can effectively reduce the resistivity);

[0010] (2) Chemical vapor infiltration densification treatment: Propylene or natural gas is used as raw material to be cracked at high temperature, and the heating element preform after drying and hardening is subjected to chemical vapor infiltration densification treatment to a density of 1.0-1.2 g / cm 3 (The carbon densified by chemical vapor deposition is pyrolytic carbon. Compared with impregnated carbon, pyrolytic carbon has higher density, better crystallization performance, and is easier to graphitize, thus obtaining a carbon structure with low resistivity);

[0011] (3) Asphalt or resin impregnation-carbonization densification treatment: Using asphalt or resin as an impregnating agent, the heating element preform treated in step (2) is placed in an impregnation tank for a period of time, and then transferred to a carbonization furnace for carbonization treatment;

[0012] (4) High vacuum high temperature graphitization process: The heating element preform is subjected to densification treatment in step (3) to a density of ≥1.65 g / cm 3Afterwards, the preform is subjected to a high-vacuum high-temperature graphitization treatment, wherein the high temperature is 2500-2600° C. (research has found that the present invention performs graphitization treatment at the above temperature, and the obtained carbon / carbon heating element has both low resistivity and high tensile strength, and has excellent resistance stability at room temperature and high temperature);

[0013] (5) Mechanical processing technology: The carbon / carbon heating element obtained by high-vacuum high-temperature purification treatment in step (4) is machined into a non-uniform thickness ring-shaped belt with a constant inner diameter and an outer diameter that gradually decreases from bottom to top; during the crystal pulling process, heat flow is likely to occur inside the silicon solution, which washes the wall of the quartz crucible, causing the crystal to contain more oxygen. In the subsequent processing, oxygen will precipitate to form impurities, resulting in concentric circles and black chip problems, which reduces the conversion efficiency of N-type battery cells. The annular heating body of the present invention adopts the above-mentioned non-uniform thickness structure. The cross-sectional area of ​​the upper half of the heating element is small and the heat generation is large; the cross-sectional area of ​​the lower half is large and the heat generation is small, so that less oxygen at the bottom will enter the crystal rod, which can effectively reduce the oxygen content in the crystal pulling process and prevent the concentrated breakage of carbon fibers, the obstruction of electron transmission, and the accumulation of current to cause sparks.

[0014] (6) Preparation of corrosion-resistant conductive coating: First, prepare a layer of CVD coating or SiC coating on the surface of the carbon / carbon heating element machined in step (5), then put it into a mixture, treat it at high temperature under an inert atmosphere for a period of time, and take it out after cooling to room temperature. To obtain a single crystal furnace carbon / carbon heating element with low resistance, high resistance stability coefficient, high strength, low oxygen content, and resistance to silicon corrosion; the mixture contains silicon powder and molybdenum powder.

[0015] Preferably, in step (1), the carbon cloth is a non-woven cloth or a plain carbon cloth, and the web is a short fiber web prepared by chopping carbon fibers and mechanically combing them into a web;

[0016] In the heating element preform, the needle density is 35 to 40 needles / cm 2 .

[0017] Preferably, in step (1), the density of the obtained heating element preform is 0.45 to 0.55 g / cm 3 .

[0018] Preferably, in step (1), the temperature of the drying and hardening treatment is (250±20)°C and the time is 1 to 3 hours.

[0019] The present invention performs drying and hardening on the heating element preform at the above temperature and time to drain the moisture in the preform, thereby preventing the preform from being deformed in subsequent steps.

[0020] Preferably, in step (2), the high temperature refers to a temperature of 850-1200°C.

[0021] Preferably, in step (3), the impregnation pressure of the heating element preform in the impregnation tank is 1.0 to 2.0 MPa;

[0022] The temperature of the carbonization treatment is (900±10)°C and the time is 3 to 5 hours.

[0023] Preferably, in step (4), the high vacuum degree refers to a vacuum degree below -0.090 MPa.

[0024] Preferably, in step (6), the temperature of the high temperature treatment is (2023±50)°C and the time is 2 to 3 hours.

[0025] The traditional coatings used in carbon / carbon composite materials for single crystal furnaces are CVD coatings, thermal sprayed Si or SiC coatings, but the heating element, as a heating functional part, is different from other structural components in the single crystal furnace and is the area with the highest heat in the entire thermal field. Therefore, silicon vapor corrosion is the most serious, and it is difficult to solve the long-term corrosion problem of the heating element by only using traditional coatings. In order to improve corrosion resistance, the present invention has tried corrosion-resistant coatings of different materials, but since the single crystal furnace has strict content requirements for ash content, especially metal element content, preliminary experiments have proved that only metal molybdenum does not affect the crystal pulling effect, and other metals are not. At the same time, if a molybdenum disilicide coating is directly prepared on the carbon / carbon heating element, due to different thermal expansion coefficients, the coating is easy to peel off, which will reduce the service life. Therefore, the present invention first prepares a CVD coating or SiC coating whose thermal expansion coefficient matches the carbon / carbon composite material on the surface of the carbon / carbon composite material, and then immerses it in the mixture, keeps it at high temperature for a period of time, generates MoSi2 on the surface of the CVD coating or SiC coating, and prepares a corrosion-resistant conductive composite coating. In addition, the corrosion-resistant coating prepared by the present invention also has conductive properties and will not affect the electron transmission in the heating element.

[0026] Preferably, in step (6), the mass ratio of silicon powder to molybdenum powder in the mixture is 4:1 to 6:1. Studies have shown that the mass ratio of silicon powder to molybdenum powder in the mixture affects the thickness and porosity of the coating, thereby affecting the corrosion resistance. The mixture composed of the above ratio has a corrosion-resistant conductive coating with better corrosion resistance.

[0027] The present invention also provides a carbon / carbon heating element for a single crystal furnace, which is prepared by the above preparation method.

[0028] The beneficial effects of the present invention are at least:

[0029] 1) The present invention provides a method for preparing a carbon / carbon heating element for a single crystal furnace. The long fibers in the heating element preform are equivalent to a highway for resistance transmission, which can effectively reduce the resistivity of the heating element. The mesh layer provides a source of needle-punched vertical fibers, which improves the interlayer bonding strength of the preform. By optimizing the content ratio of the two, excellent conductivity and strength are taken into account;

[0030] 2) The present invention provides a method for preparing a charcoal / charcoal heating element for a single crystal furnace, which adopts a gas-liquid combined densification method. Studies have found that the pyrolytic charcoal formed by chemical vapor infiltration densification has high density and good crystallization properties. It nucleates and grows on the surface of the carbon fiber and grows around the carbon fiber, preferentially filling the fiber pores. However, when the inter-bundle pores and inter-layer pores are too large, there are not enough nucleation sites, and a large number of inter-bundle pores and inter-layer pores remain, which will cause carrier transport to be obstructed. The present invention controls the ratio of pyrolytic charcoal to impregnated charcoal, and further combines asphalt or resin impregnation-carbonization densification. The asphalt charcoal or resin charcoal generated by the present invention is granular, which is easier to fill the remaining inter-bundle and inter-layer large pores, thereby overcoming the technical disadvantage of obstructed carrier transport;

[0031] 3) The present invention provides a method for preparing a carbon / carbon heating element for a single crystal furnace, wherein the heating element is preferably subjected to non-uniform thickness machining with the outer diameter gradually decreasing from bottom to top, so that the upper half of the heating element generates a large amount of heat and the lower half generates a small amount of heat, which can effectively reduce the oxygen content during the crystal pulling process and prevent the concentrated breakage of carbon fibers, the obstruction of electron transmission, and the accumulation of current leading to sparking;

[0032] 4) The present invention provides a method for preparing a carbon / carbon heating element for a single crystal furnace, wherein the heating element product after machining is subjected to a conductive and corrosion-resistant composite coating, which can effectively adjust the resistance of the heating element and improve the corrosion resistance in a silicon vapor environment;

[0033] 5) The present invention provides a method for preparing a charcoal / charcoal heating element for a single crystal furnace. The heating element is integrally formed and is conveniently connected to a foot plate and an electrode for installation, thereby reducing the risk of ignition and extending the service life of the charcoal / charcoal heating element. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram of the structure of the carbon / carbon heating element prepared by machining according to Example 1 of the present invention. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention is described clearly and completely below. The following embodiments are used to illustrate the present invention, but are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in the field or the product instructions are used.

[0036] In the following examples, information of the raw materials used is shown in Table 1.

[0037] Table 1

[0038] raw material Brand factory 12K carbon cloth SYZ49S-12K plain carbon cloth Zhongfu Shenying Net tire SYZ49S fiber 50mm Zhongfu Shenying

[0039] Example 1

[0040] Embodiment 1 provides a method for preparing a carbon / carbon heating element for a single crystal furnace, and the specific steps are as follows:

[0041] (1) 12K carbon cloth and mesh tire are alternately laid, with a total thickness of 36 mm, and needle-punched in the interlayer direction with a needle-punching density of 35 needles / cm 2 , a three-dimensional structure heating element preform is made, and the preform density is (0.5±0.02)g / cm 3 , wherein the content of carbon cloth is 80wt%, the content of mesh tire is 20wt%, and the preform is dried and hardened at a temperature of 250°C for 2h;

[0042] (2) Chemical vapor infiltration densification process: Propylene is used as raw material and cracked at a high temperature of 1000°C, and the preform is subjected to vapor infiltration densification treatment to a density of 1.2 g / cm 3 ;

[0043] (3) The heating element after chemical vapor infiltration densification treatment was placed in an asphalt impregnation tank and impregnated for 5 hours at an impregnation pressure of 1.6 MPa. After impregnation, it was transferred to a carbonization furnace for carbonization treatment at a carbonization temperature of 900°C and a carbonization time of 4 hours.

[0044] (4) The density of the heating element after densification in step (3) is 1.65 g / cm 3 , subjecting the preform to a high-vacuum high-temperature graphitization treatment in a vacuum continuous furnace, wherein the high temperature refers to a temperature of 2600° C., the high vacuum refers to a vacuum degree of ≤-0.090 MPa, and the treatment time is 2 hours;

[0045] (5) The carbon / carbon heating element that has been graphitized at high temperature and high altitude is machined using a lathe. The machined carbon / carbon heating element is shown in FIG. Figure 1 , its height is 280mm, resistance is 23±2mΩ, it includes an annular heating body and a connecting plate, the height of the annular heating body is 220mm, the number of heating body petals is 18, the petal width is 55mm, the groove width is 20mm, the inner diameter remains unchanged, and the outer diameter gradually decreases from 1096mm to 1088mm from bottom to top; the connecting plate is arranged on the lower side of the annular heating body, with a height of 60mm, an inner diameter consistent with the annular heating body, and an outer diameter of 1096mm. A through hole is arranged on the connecting plate for connecting and fixing the charcoal / charcoal heating element and the heating body legs.

[0046] (6) A corrosion-resistant conductive coating is prepared on the surface of the heating element after machining. The specific preparation method is as follows: first, a layer of CVD coating is prepared on the surface of the carbon / carbon heating element after machining in step (5) (propylene is used as the carbon source, and the reaction is carried out at 980°C for 20 hours in an atmosphere with a nitrogen to argon ratio of 1.2:1), and then the mixture is put into the mixture and treated at a high temperature of 2023°C for 2 hours under argon, and then taken out after cooling to room temperature; the mixture is silicon powder and molybdenum powder in a mass ratio of 4.5:1.

[0047] By only changing the graphitization treatment temperature in step (4) of Example 1, the graphitization degree and tensile strength results of the obtained carbon / carbon heating element are shown in Tables 2 and 3 below.

[0048] Table 2

[0049]

[0050]

[0051] Table 3

[0052] Graphitization treatment temperature (℃) Tensile strength(MPa) 2500℃ 60.7 2600℃ 59.8 3000℃ 36.3

[0053] It can be seen from Table 2 and Table 3 that when the graphitization temperature is above 2500°C, the graphitization degree of the obtained carbon / carbon heating element is significantly improved (the higher the graphitization degree, the lower the resistivity), but when the graphitization temperature reaches 3000°C, the tensile strength decreases significantly. Therefore, when the graphitization treatment is carried out at 2500-2600°C, the obtained carbon / carbon heating element takes into account both low resistivity and high tensile strength.

[0054] Example 2

[0055] The difference between Example 2 and Example 1 is that in step (3), furan resin is used as an impregnating agent for impregnation-carbonization densification treatment. Specifically, step (3) is:

[0056] (3) The heating element after chemical vapor infiltration densification treatment is placed in a resin impregnation tank and impregnated for 5 hours at an impregnation pressure of 1.2 MPa. After impregnation, it is transferred to a carbonization furnace for carbonization treatment at a carbonization temperature of 900°C and a carbonization time of 4 hours.

[0057] The density of the heating element after densification in step (3) is 1.7 g / cm 3 .

[0058] Example 3

[0059] The difference between Example 3 and Example 1 is that in step (6), the CVD coating prepared on the surface of the carbon / carbon heating element is replaced by a SiC coating. Specifically, step (6) is:

[0060] A corrosion-resistant conductive coating is prepared on the surface of the heating element after machining. The specific preparation method is as follows: first, a layer of SiC coating is prepared on the surface of the carbon / carbon heating element after machining in step (5) (the densified carbon / carbon surface is plasma sprayed with a Si coating, and then reacted at 1800°C for 3 hours under argon protection), and then put into the mixture, high-temperature treated at 2023°C for 2 hours under argon, and then taken out after cooling to room temperature; the mixture is silicon powder and molybdenum powder in a mass ratio of 4.5:1.

[0061] Comparative Example 1

[0062] The difference between Comparative Example 1 and Example 1 is that the raw material of Comparative Example 1 is high-density isostatic graphite, which is machined into a heating element having the same shape and size as Example 1.

[0063] Comparative Example 2

[0064] The only difference between Comparative Example 2 and Example 1 is that in step (4), the temperature during the high vacuum high temperature graphitization treatment is 1800°C.

[0065] The bridge method was used to test the room temperature resistance of the heating element obtained in Comparative Example 2. The resistance was 43mΩ, which was much larger than the normal working resistance value. The electric control cabinet exceeded the voltage requirement. In addition, the resistance stability was poor during use, and the crystal could not be pulled normally.

[0066] Comparative Example 3

[0067] The difference between Comparative Example 3 and Example 1 is that in step (6), the CVD coating is only prepared on the surface of the carbon / carbon heating element. Specifically, step (6) is:

[0068] A CVD coating is prepared on the surface of the machined carbon / carbon heating element in step (5) by using propylene as the carbon source and reacting at 980°C for 20 hours in an atmosphere with a nitrogen to argon ratio of 1.2:1.

[0069] After the CVD coating was prepared in Comparative Example 3, the porosity of the carbon / carbon material decreased from 15% to 12%, which did not show a significant decrease. However, during the crystal pulling process, silicon vapor seriously corroded the heating element, and the resistance value increased rapidly, reducing the service life.

[0070] Comparative Example 4

[0071] The only difference between Comparative Example 4 and Example 1 is that the carbon / carbon heating element obtained by machining in step (5) is a traditional equal-thickness structure. Specifically, its outer diameter remains unchanged from bottom to top, which is 1096 mm.

[0072] The crystal rod pulled out by using the heating element structure designed in Example 1 of the present invention has an impurity content of 7ppm after testing; while the crystal rod pulled out by using the heating element of the traditional structure in Comparative Example 4 has an impurity content of more than 10ppm after testing.

[0073] Test example

[0074] The heating elements prepared in the embodiments and comparative examples were subjected to performance tests, and the test results are shown in Table 4.

[0075] Among them, density: measure the mass and volume of the sample respectively, and divide the mass by the volume to get the density;

[0076] Flexural strength: According to GB / T 40398.2-2021 Test methods for carbon-carbon composite carbon materials Part 2 Bending properties test;

[0077] Thermal conductivity: According to GB / T 8722-2019 thermal conductivity determination method of carbon materials;

[0078] Ash content: According to QJ 2509-1993 carbon / carbon composite material ash content test method;

[0079] Room temperature resistivity: According to GB / T24525-2009 carbon material resistivity determination method;

[0080] The high temperature resistivity is the value obtained through the upper furnace electrical control cabinet.

[0081] Table 4

[0082] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 <![CDATA[Density (g / cm 3 )]]> 1.65 1.7 1.68 1.8 1.68 Bending strength MPa 148 130 146 50 160 Thermal conductivity MPa 138 110 135 120 120 Ash content PPm 163 193 160 200 210 Room temperature resistivity μΩ·m 12 14 12.2 11 43 High temperature resistivity μΩ·m 10 10.5 9.8 9 20

[0083] It can be seen from Table 4 that the carbon / carbon heating elements prepared in Example 1, Example 2 and Example 3 are basically equivalent to the carbon / carbon heating element prepared in Comparative Example 1 using traditional high-density isostatic graphite in terms of thermal conductivity, ash content, room-temperature resistivity and high-temperature resistivity, but the bending strength is significantly improved, while the density is slightly decreased and the weight is lighter; the carbon / carbon heating elements prepared in Example 1, Example 2 and Example 3 are basically equivalent to the carbon / carbon heating element prepared in Comparative Example 2 in terms of density, bending strength, thermal conductivity and ash content, but the room-temperature resistivity and high-temperature resistivity are significantly reduced. The lower resistivity can reduce the difficulty of designing the power supply and heating program for designers and improve the efficiency during heating.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a carbon / carbon heating element for a single crystal furnace, characterized in that: The following steps are involved: (1) Alternately layering carbon cloth and mesh tires, needle punching in the interlayer direction, to form a three-dimensional structure heating element preform, and then drying and hardening the obtained heating element preform; in the heating element preform, the content of carbon cloth is 70-90wt%, and the content of mesh tire is 10-30wt%; (2) Chemical vapor infiltration densification treatment: Propylene or natural gas is used as raw material to be cracked at high temperature, and the heating element preform after drying and hardening is subjected to chemical vapor infiltration densification treatment to a density of 1.0-1.2 g / cm 3 ; (3) Asphalt or resin impregnation-carbonization densification treatment: Using asphalt or resin as an impregnating agent, the heating element preform treated in step (2) is placed in an impregnation tank for a period of time, and then transferred to a carbonization furnace for carbonization treatment; (4) High vacuum high temperature graphitization process: The heating element preform is subjected to densification treatment in step (3) to a density of ≥1.65 g / cm 3 Afterwards, the preform is subjected to a high vacuum high temperature graphitization treatment, wherein the high temperature is 2500-2600° C.; (5) Mechanical processing technology: the carbon / carbon heating element obtained by high vacuum and high temperature purification is machined into a non-uniform thickness ring-shaped belt with a constant inner diameter and an outer diameter that gradually decreases from bottom to top; (6) Preparation of corrosion-resistant conductive coating: A layer of CVD coating or SiC coating is prepared on the surface of the machined carbon / carbon heating element, and then placed in a mixture and treated at high temperature for a period of time under an inert atmosphere; the mixture contains silicon powder and molybdenum powder.

2. The method for preparing a carbon / carbon heating element for a single crystal furnace according to claim 1, characterized in that: In step (1), the carbon cloth is a non-woven cloth or a plain carbon cloth, and the web is a short fiber web prepared by chopping carbon fibers and mechanically combing them into a web; In the heating element preform, the needle density is 35 to 40 needles / cm 2 .

3. The method for preparing a carbon / carbon heating element for a single crystal furnace according to claim 1 or 2, characterized in that: In step (1), the density of the obtained heating element preform is 0.45-0.55 g / cm 3 ; And / or, the temperature of the drying and hardening treatment is (250±20)°C and the time is 1 to 3 hours.

4. The method for preparing a carbon / carbon heating element for a single crystal furnace according to claim 1 or 2, characterized in that: In step (3), the immersion pressure of the heating element preform in the immersion tank is 1.0 to 2.0 MPa; The temperature of the carbonization treatment is (900±10)°C and the time is 3 to 5 hours.

5. The method for preparing a carbon / carbon heating element for a single crystal furnace according to claim 1 or 2, characterized in that: In step (6), the temperature of the high temperature treatment is (2023±50)°C and the time is 2 to 3 hours.

6. The method for preparing a carbon / carbon heating element for a single crystal furnace according to claim 1 or 2, wherein in step (6), the mass ratio of silicon powder to molybdenum powder in the mixture is 4:1 to 6:

1.

7. A carbon / carbon heating element for a single crystal furnace, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Carbon / carbon compound material heating element and production technology thereof

    CN101386547A

  • Method for preparing carbon / carbon composite material antioxidation coating layer

    CN101565328A

  • Method for preparing carbon / carbon heat shields used for polysilicon hydriding furnances

    CN101638322A

  • Preparation method of C / C (carbon / carbon) composite material slider for pantograph

    CN104692823A

  • Method and heater for improving quality of monocrystal silicon grown by Czochralski method

    CN104818524A